Bimbingan Klasikal Berbasis Dzikir untuk Meningkatkan Keterampilan Emosi Anak Panti Asuhan Rumah Harapan Samarinda - Nursa'adah, Yessi; Almatubah; Nurfadilah, Rohmah; Atussolihah, Mar; Savitri, Rahmi Dwi; Repalina; Indrayani, Dhea; Kusuma, Rudy Hadi (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This study aims to enhance emotional regulation skills among orphanage children through a classical guidance approach based on dzikir (Islamic remembrance). Children living in orphanages often face limitations in emotional caregiving, which affects their affective balance. The activity was carried out in two face-to-face sessions at Rumah Harapan Orphanage in Samarinda, involving 15 children aged 8–12 years. The methods used included interactive lectures, group discussions, observations, games, and dzikir practices such as "Subhanallah", "Alhamdulillah", and "Astaghfirullah". The results indicated an increase in the children’s self-awareness and their ability to manage emotions through an Islamic spiritual approach. This classical guidance created a safe and educational space, actively engaging the children in understanding and applying dzikir as a positive self-regulation strategy.